Survey on prevalence of bovine trypanosomiosis in Wonchi Woreda, South West Shoa Zone, Central Ethiopia - Dula, G.; Solomon, R.; Leta, H.; Bekele, L.; Yilma, G.; Gemechu, L.; Deresa, B.; Kabeta, T. (Scientific Journal of Zoology, 2014)
Bovine trypanosomosis is one of the most prevalent and important disease in Ethiopia limiting livestock productivity and agricultural development. A cross-sectional survey of bovine trypanosomosis was conducted from December 2013 to May 2013 in Wonchi district of South West Shoa zone to estimate the prevalence of bovine trypanosomosis and assess the risk factors associated with its occurrence. Blood samples were collected from 384 randomly sampled cattle of four conveniently selected kebeles of the district. Thin blood smear was made from the collected blood samples using Giemsa stain. Of the animals examined, the overall prevalence of bovine trypanosomiosis was found to be 2.1%. The highest prevalence was observed in Haro Kono (4.3%) followed by Meti Walga (1.7%). There was statistically significant difference (P<0.05) in the prevalence of the disease among the different kebeles. Older animals were found to be significantly affected than the younger ones. However, no statistically significant variation observed in the prevalence of the disease between the two sexes. Although the present study showed a low level of prevalence in the study area using a test with poor sensitivity; nevertheless, vagarious disease, mitigation strategies is warranted owing to the economic implication of the disease.